ÖZEL DİL TARTIŞMASI - Şeref Günday (Felsefe Dünyası)
In this investigation we tried to give a brief introduction about Wittgenstein's "private language arqument". At the begining we wanted to show why this subject is important for philosophy. Later on we defined the concept of "private language". The main concern for Wittgenstein related to private language is solipsism. But, while escaping from solipsism Wittgenstein disturbed the privacy of the mind. At the and, we gave our ideas about the subject that privacy is essential part of human mind. But, of course, Wittgenstein's questions about "private language" are meaninfull.